Underestimation of global soil CO2 flux measurements caused by near-surface winds - Feng, Lingxia; Jiang, Junjie; Hu, Junguo (Frontiers in Forests and Global Change, 2024)
Soil respiration (Rs) is the largest source of atmospheric CO2, and an accurate understanding of the relationship between near-surface winds, CO2 release from the soil surface, and measurement methods is critical for predicting future atmospheric CO2 concentrations. In this study, the relationship between wind speed and soil CO2 fluxes is elucidated on a global scale through meta-analysis, and the flux measurement methodology is further explored in conjunction with the results of a controlled trial to clarify the uncertainty of the measurement results. The results indicate that near-surface wind speed is positively correlated with soil CO2 release and that near-surface winds result in increased soil CO2 gas release. Wind disturbance affects both the concentration gradient and gas chamber measurements, and the lower calculated soil CO2 release conflicts with the notion that the wind pump effect and Bernoulli effect of negative pressure cause a greater surface gas exchange. The results of the log-response ratios indicate that near-surface winds lead to an underestimation of 12.19%-19.75% in widely-used gas chamber method measurements. The results of this study imply that some of the current Rs measurements are biased and that the influence of near-surface winds on Rs measurements needs to be urgently addressed to assess the terrestrial carbon cycle more accurately and develop climate change response strategies.